2019
DOI: 10.1038/s41439-019-0065-7
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical and genetic characteristics of 14 patients from 13 Japanese families with RPGR-associated retinal disorder: report of eight novel variants

Abstract: Variants in the retinitis pigmentosa GTPase regulator (RPGR) gene are a major cause of X-linked inherited retinal disorder (IRD). We herein describe the clinical and genetic features of 14 patients from 13 Japanese families harboring RPGR variants in a nationwide cohort. Comprehensive ophthalmological examinations were performed to classify the patients into one of the phenotype subgroups: retinitis pigmentosa (RP) and cone rod dystrophy (CORD). The mean age of onset/at examination was 13.8/38.1 years (range, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…31,32 A common ground was found instead regarding RPGR variants located toward the 3 end of ORF15, which were more frequently associated with milder XL Cone Rod Dystrophy (CRD) / XL Cone Dystrophy (CD) phenotypes. 25,30,[33][34][35] Finally, some RPGR variants in exons 1 to 14 were reported in patients with RP presenting progressive hearing loss, sinusitis, and chronic recurrent respiratory tract infections, [36][37][38] in line with the more widespread expression of the RPGR [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] isoform and its essential ciliary function in other organs apart from retina. 39,40 In this study, we report the clinical and genetic findings in a cohort of 48 male patients of Italian origin with XLRP caused by variants in RPGR.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…31,32 A common ground was found instead regarding RPGR variants located toward the 3 end of ORF15, which were more frequently associated with milder XL Cone Rod Dystrophy (CRD) / XL Cone Dystrophy (CD) phenotypes. 25,30,[33][34][35] Finally, some RPGR variants in exons 1 to 14 were reported in patients with RP presenting progressive hearing loss, sinusitis, and chronic recurrent respiratory tract infections, [36][37][38] in line with the more widespread expression of the RPGR [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] isoform and its essential ciliary function in other organs apart from retina. 39,40 In this study, we report the clinical and genetic findings in a cohort of 48 male patients of Italian origin with XLRP caused by variants in RPGR.…”
mentioning
confidence: 99%
“…In particular, the terminal exon (open reading frame 15; ORF15 ) of the RPGR ORF15 isoform contains a repetitive, purine-rich sequence coding for a low complexity stretch of 567-aa with a high glutamic acid and glycine (Glu/Gly) content. 23 Until now, more than 350 sequence variants have been described in RPGR 25 and almost 60% of them are found in ORF15 . 26 The high mutation frequency in ORF15 (mainly small deletions or duplications) is most likely due to the nucleotide composition and repetitive nature of its sequence, which might induce errors during DNA replication.…”
mentioning
confidence: 99%
“…It is possible that AS is regulated by m6A RNA methylation. Mutations in rpgra are associated with atrophic macular degeneration and primary cilia dyskinesia (Bukowy-Bieryllo et al 2013;Mawatari et al 2019) and splicing mutations in AHR have been associated with the development of retinitis pigmentosa (Zhou et al 2018). These results suggest that transcripts associated with AHR signaling are regulated by the m6A RNA modifications.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, the eyes with the RPGR gene had the steepest curvature compared to the other ciliopathy-related Downloaded from iovs.arvojournals.org on 11/03/2020 genes. Earlier studies have reported the findings in RPGR eyes complicated by high myopia [28][29][30][31] and on the relationship between RPGR-related RP and pathologic myopia. 31,32 However, the macular curvature in these eyes was not mentioned.…”
Section: Discussionmentioning
confidence: 99%